The impact of burden sharing rules on the voluntary provision of public goods - Martin Kesternich; Andreas Lange; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We investigate how burden sharing rules may impact the voluntary provision of a public good which generates heterogeneous benefits to agents. We compare different rule-based contribution schemes that are based on the principle of the smallest common denominator: all agents can suggest a minimum provision level of the public good that is allocated across agents according to some predetermined rule. We find that rule-based contribution schemes significantly increase payoff levels relative to the VCM. Important differences exist between the rules. Contrary to theory predictions, the equal-payoff rule Pareto-dominates all other rules. This also holds relative to a scheme where different types of players separately can determine their minimum contribution levels. Our results lend insights into the efficient institutional design for voluntary private provision of public goods, and how burden sharing rules interact with efficiency when agents are heterogeneous.
urn:nbn:de:bsz:180-madoc-323070
Keywords: C72; C92; H41; 330; public goods; institutions; minimum contribution rules; cooperation; heterogeneity; Öffentliches Gut; Lastenverteilung; Nichtkooperatives Spiel; Test